The crystal structure of 1,1′-(2,5-dimethylpyrazine-1,4-diyl)bis(ethan-1-one), C10H14N2O2 - Wang Jinfeng (Zeitschrift für Kristallographie - New Crystal Structures)
C10H14N2O2, monoclinic, C2/c (no. 15), a = 15.7853(7) Å, b = 8.5036(4) Å, c = 31.4964(17) Å, β = 90.371(2)°, V = 4,227.7(4) Å3, Z = 8, Rgt(F) = 0.0451, wRref(F2) = 0.1611, T = 655 K.